TEACHERS’ READINESS TO IMPLEMENT THE ACQUISITION OF TRANSVERSAL SKILLS IN THE CONTEXT OF THE NEW STANDARD - Petere, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In today’s rapidly changing world, when information technologies are developing very fast, a new change of the paradigm of the educational system is needed. It means that a teacher’s pedagogical activities also have to change – from an educator to a cooperation partner in the teaching/learning process. National Centre for Education (NCE)  has worked out a new ”Competence approach to teaching/learning content”, the aim of which is to ensure the acquisition of the content of general education based on competence approach, and which embraces all stages in education.The objective of the article is to reveal the essence of competence approach and the readiness of primary school teachers to implement the acquisition of transversal skills in teaching/learning process and when planning curricula.In order to obtain data, semi- structured interviews, observation, the analysis of documents have been used. According to the research results, part of the teachers finds it difficult to change their style of conducting the teaching/learning process. Explanation and task formulation dominate without involving pupils in discussions.